(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
Blogs are a locus of tension between global and local, between online and offline, a virtual place where individuals meet, interact, express themselves in a process of (re)territorialisation among the identity fragmentation of post-modernity and the internet itself. This article briefly debates key concepts of cyberculture, space-time compression, identity fragmentation, among others, in order to understand the role of a (re)territorialisation and (re)signification virtual space or settlement through sharing, linkania and the formation of strong ties among individuals forming virtual communities.